Load frequency control of multi area system under deregulated environment using artificial gorilla troops optimization - Sambugari Anil Kumar; M. Siva Sathya Narayana Varma; K. Jithendra Gowd (Bulletin of Electrical Engineering and Informatics, 2022)
The artificial gorilla troops method is utilized in the tilt integral derivative (TID) controller that is discussed in this paper in order to adorn the load frequency control (LFC) in the restructured thermal-hydal system. The controller is implemented in simulink. In this study, a mathematical definition of the social life of gorillas and innovative methods for exploring and exploiting gorilla habitats are presented. By applying step load perturbations and using integral square error as the evaluation method, the dynamic properties of the system can be determined. It is clear that the newly developed method of optimizing artificial gorilla troops performs better than the grey-wolf optimization technique (GTO). In this paper, the TID controller and the proportional integral derivative (PID) controller are contrasted with regard to a variety of optimization strategies inorder to compare different power transcations.